Evaluation of resilience-based sustainable soil management database parameter for soil quality assessments of selected histosols in Sarawak - Wee, Boon Siong. (Universiti Malaysia Sarawak (UNIMAS), 2001)
Histosols is a dynamic entity and spatial variability is extremely complicated. Building a database for soil quality assessment of Histosols under agriculture will need substantial amount of information which is reliable. The objective of this study is to examine the physical, chemical, and biological parameters used in soil quality assessmnet to histosols. The parameters selected for this study are pH, organic carbon, total nitrigen, CEC exchangeable cations, electronic conductivity, available phosphorus, trace elements, bulk density degree of decomposition, rubbed firber content, soil depth, hydraulic conductivity, and soil respiration.